Dimensions of space in business network research - Jan-åke Törnroos; Aino Halinen; Christopher J. Medlin (Elsevier, 2022)
Interactive processes constitute a core notion in business exchange, leading to the concepts of relationships and networks. The constitution of process, comprising unfolding events, activities, and connected structures, relies on difference in space and time.While research has been devoted to time, the concept of space has thus far remained largely unexplored within business network research.This conceptual paper focuses on spatial dimensions for conducting research according to the IMP business network approach. Business actors create connected relationships and networks that exist and change as continuous emerging spatial structures and as mental maps in the managerial mindset. These relational network processes and structures are located, distributed and experienced in and across space. Drawing on economic geography and conceptual frameworks from the business network approach, we propose new dimensions and conceptualizations of space for the study of these networks. The paper delivers proposals to extend our current understanding of business networks as emerging and changing spatio-temporal entities with implications for theorydevelopment, research and practice.